Identifikasi Social Power dalam Karakteristik Kiai sebagai Rujukan Kualitas Diri Konselor - Maya Tsuroya Alfadla; Andi Mappiare- AT; Diniy Hidayatur Rahman (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The figure of the Kiai has social power for both students and the community. The purpose of this research is to find the meaning of the students towards the Kiai’s social power which will be adopted into the quality of the counselor. This study uses a qualitative approach with symbolic interactionism. Researchers get the meanings that are built from interactions with individuals in human society. Data collection used through interviews, observations, and documents. The results of interpreting student to Kiai’s social power that can be adopted into the quality of the counselor are: (1) Strong spirituality oriented to happiness in the world and the hereafter; (2) Models means that the counselor's behavior becomes a medium of behavior; (3) Social Influence and devotion to society.Abstrak: Sosok Kiai memiliki social power bagi santri maupun kalangan masyarakat. Tujuan penelitian ini adalah menemukan pemaknaan santri terhadap social power yang dimiliki Kiai yang akan diadopsi menjadi kualitas diri konselor. Penelitian ini menggunakan kualitatif dengan pendekatan interaksionisme simbolik yakni peneliti menggali makna-makna yang terbangun dari interaksi bersama individu dalam masyarakat manusia. Pengumpulan data yang digunakan melalui wawancara, observasi, dan dokumen. Hasil pemaknaan social power santri yang dapat diadopsi menjadi kualitas diri konselor adalah (1) spiritualitas yang kuat berorientasi kebahagiaan dunia dan akhirat; (2) teladan artinya perilaku konselor menjadi media mengajarkan perilaku; (3) pengaruh sosial dan pengabdian diri pada masyarakat.